A systematic review and meta-analysis of concussion in Rugby Union - Gardner, A. J.; IIverson, G. L.; Williams, W. H.; Baker, S.; Stanwell, P. (Sports Medicine, 2014)
Background: Rugby Union, a popular full-contact sport played throughout the world, has one of the highest rates of concussion of all full-contact sports. Objective: The aim of the current review was to systematically evaluate the available evidence on concussion in Rugby Union and to conduct a meta-analysis of findings regarding the incidence of concussion. Methods: Articles were retrieved via a number of online databases. The current review examined all articles published in English up to May 2014 pertaining to concussion in Rugby Union players. The key search terms included `Rugby Union`, `rugby`, `union`, and `football`, in combination with the injury terms `athletic injuries`, `concussion`, `sports concussion`, `sports-related concussion`, `brain concussion`, `brain injury`, `brain injuries`, `mild traumatic brain injury`, `mTBI`, `traumatic brain injury`, `TBI`, `craniocerebral trauma`, `head injury`, and `brain damage`. Results: The final search outcome following the eligibility screening process resulted in the inclusion of 96 articles for this review. The meta-analysis included a total of 37 studies. The results of the meta-analysis revealed an overall incidence of match-play concussion in men`s rugby-15s of 4.73 per 1,000 player match hours. The incidence of concussion during training was 0.07 per 1,000 practice hours. The incidence of concussion in women`s rugby-15s was 0.55 per 1,000 player match hours. In men`s rugby-7s match-play, concussion incidence was 3.01 per 1,000 player match hours. The incidence of concussion varied considerably between levels of play, with elite level play recording a rate of 0.40 concussions per 1,000 player match hours, schoolboy level 0.62 concussions per 1,000 player match hours, and the community or sub-elite level recording a rate of 2.08 concussions per 1,000 player match hours. The incidence of concussion in men`s rugby-15s as a function of playing position (forwards vs. backs) was 4.02 and 4.85 concussions per 1,000 player match hours, respectively. Conclusions: Concussion is a common injury sustained and reported in match play and to a lesser extent during practice by Rugby Union players. Based on the available published data, there appears to be a variation in risk of concussion across level of play, with the sub-elite level having the greatest incidence of injury. Future research focused on studying the acute consequences and best management strategies in current players, and the potential longer term outcomes of concussion in retired players, is needed. A focus on the areas of prevention, injury identification, and medical management, and risk for long-term outcomes will be of benefit to current athletes.